Music and Mental Well-Being of Older Adults - Panicha Ponprasit; Juthatip Wiwattanapantuwong; Arunya Tuicomepee (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2021)
This research study documents and empirical research related to the role of music and mental well-being of the older adults. From the review of literatures during 1999-2019, there were 23 qualitative and quantitative studies (from 1,478 studies) which met the criteria. The studies were formed in two groups which explore the roles of music in affecting older people’s mental well-being. Those studies mention that music related activities can develop the senses of purpose, free will and autonomy, and social affirmation in older people’s lives. Besides, music can enhance older people’s happiness, emotions, body and cognitive function development. In addition, the literature also reveals the meaning of music and its activities for older adults as a perception of identity, beauty and aesthetics, relaxing and relieving stress in daily life and a way of motivation for older adults. These benefits can fulfill older people to strengthen their physical and mental health and live their lives happily as an aspect of older people with mental well-being.